Penerapan E-LKPD berbasis Project Based Learning (PjBL) untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Riska Wahyuni; Azwar Siregar; Ghina Salwa; Gracia Hillary; Jernita Napitupulu; Maharani Siregar; Nur Indah; Silvia Harahap (Journal of Natural Sciences, 2021)
The purpose of this study was to determine the increase in student motivation and learning outcomes by implementing E-LKPD based on Project Based Learning (PjBL) on the respiratory system material in humans in online learning in class VIII-B of SMP Negeri 3 Tarutung T.P. 2020/2021. The research method used is Classroom Action Research (CAR). This research was conducted in 2 cycles. The results of the student learning motivation questionnaire in the first cycle were 33.3% and the second cycle was 62.5% in the high category. Student learning outcomes in the first cycle 58.3% complete learning and 41.6% students do not complete learning. Whereas in the second cycle 87.5% completed learning and 18.5% did not complete the study. Thus it can be concluded that the application of PjBL-based E-LKPD on respiratory system materials in humans in online learning in class VIII-B SMP Negeri 3 Tarutung T.P. 2020/2021 can increase student motivation and learning outcomes